A Comparative Analysis of Leaf Trichomes in Diploid and In Vitro-Induced Tetraploid Patchouli (Pogostemon cablin Benth.) - Aini, Qurrotu; Widoretno, Wahyu (Graduate School, Universitas Brawijaya, 2026)
This study aimed to analyze the types, sizes, numbers, and densities of leaf trichomes in in vitro–induced tetraploid patchouli (Pogostemon cablin Benth.) plants and their diploid counterparts. Microscopic observations were conducted on four-month-old leaves obtained from stem cuttings. Both diploid and tetraploid patchouli possessed non-glandular trichomes of the simple unicellular and multicellular types, as well as glandular trichomes of the short- and long-stalked capitate and peltate types. The density of non-glandular trichomes was higher on the abaxial surface of the leaves than on the adaxial surface. Overall, tetraploid plants, particularly genotypes T2, T4, T5, and T7, exhibited higher non-glandular trichome densities than diploids, while the others showed higher densities but were not significantly different. Glandular trichomes of tetraploids were larger, although their numbers were comparable to those of diploids. The head cell diameters of capitate and peltate trichomes were generally larger in tetraploids. These findings indicate that genome duplication enhances trichome development in patchouli, leading to increased secretory capacity and improved structural defense potential against herbivores and pathogens.